ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT NASABAH MENGGUNAKAN M-BANKING BERDASARKAN TEORI TAM - Caroline, Christine Clara; Hastuti, Theresia Dwi (KEUNIS, 2021)
This study aims to determine the positive influence of Perceived Ease of Use (PEOU), Perceived Ease of Use (PEOU), Perceived Usefulness (PU), Subjective Norm (SN), Subjective Norm (SN) on Intention to Use (ITU), and To determine the positive effect of Attitude (A) on Intention to Use (ITU). The sample is 207 respondents using M-Banking in Yogyakarta. SEM AMOS is used and has an effect on attitudes (A) of M-Banking users, Subjective Norms (NS) have a positive effect on interest in using (ITU) M-Banking, Perceived ease of use (PEOU) has a positive effect on perceived benefits (PU). M-Banking, Perceived Benefit (PU) has a positive effect on Interest in Using (ITU) M-Banking, Subjective Norms (SN) has a positive effect on Perceived Benefit (PU) M-Banking, Subjective Norms (NS) there is a relationship with interest (ITU) ) M-Banking, Attitude (A) there is a relationship in (ITU) M-Banking.